2011
DOI: 10.1186/1477-7819-9-80
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy for high-risk cutaneous squamous cell carcinoma: clinical experience and review of literature

Abstract: High-risk cutaneous squamous cell carcinoma (SCC) is associated with an increased risk of metastases. The role of sentinel lymph node (SLN) biopsy in these patients remains unclear. To address this uncertainty, we collected clinical data on six patients with clinical N0 high-risk SCC that underwent SLN biopsy between 1999 and 2006 and performed a literature review of SLN procedures for SCC to study the utility of SLN biopsy. There were no positive SLN identified among six cases and there was one local and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
3
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(125 citation statements)
references
References 39 publications
4
114
3
4
Order By: Relevance
“…22,23 Our study found 6 of 26 cases (23.1%) to be SN-metastasis positive, which is within the range of past reports. No instances of regional lymph node metastasis occurred in the cases deemed SNmetastasis negative during the observational period in our study.…”
Section: Discussionsupporting
confidence: 78%
“…22,23 Our study found 6 of 26 cases (23.1%) to be SN-metastasis positive, which is within the range of past reports. No instances of regional lymph node metastasis occurred in the cases deemed SNmetastasis negative during the observational period in our study.…”
Section: Discussionsupporting
confidence: 78%
“…Several authors have examined the utility of SLNB as a method for staging patients with non-melanoma skin cancer who are at high risk for metastasis. 1,2,6 These studies suggested that it might be useful in patients with high-risk cutaneous squamous cell carcinoma. Cherpalis et al suggest that patients with lymph node metastasis may be cured by lymph node dissection and radiotherapy and SLNB would therefore be an important staging tool and in planning the right treatment for patients with high-risk cSCC.…”
Section: Introduction/backgroundmentioning
confidence: 95%
“…Risk factors for metastasis include tumor size, localization, Clark level IV and above, poorly differentiated histological subtype, immunosuppression, and perineural invasion. 2 Patients with lymph node metastasis have a 5-year survival ranging from 26 to 34% 1 The utility of sentinel lymph node biopsy (SLNB) in staging of melanoma is well established as an independent prognostic factor for survival and has proved to prolong the disease-free survival. 3e5 It has yet not shown to improve the overall survival but SLNB is still widely accepted as a minimally invasive procedure with high accuracy for detection of nodal metastases and as a diagnostic tool.…”
Section: Introduction/backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Sentinel lymph node biopsy-a minimally invasive technique for identifying occult nodal metastases-is used commonly in breast cancer and cutaneous melanoma, but the value of this method in high-risk SCC is not well established. 6,13,32,33 …”
Section: Sentinel Lymph Node Biopsiesmentioning
confidence: 99%